EFEKTIFITAS PEMANFATAAN LARUTAN PACI-PACI (LEUCAS LAVANDULAEFOLIA) TERHADAP PERKEMBANGAN POPULASI PARASIT (TRICHODINA SP) PADA IKAN LELE DUMBO (CLARIAS SP) - Abdul Haris; Andi Asran (Universitas Muhammadiyah Makassar, 2015)
This study aims to determine the effectiveness of the solution to the abundance paci- paci Trichodina sp that attack catfish. This research is expected to be material information in an effort to increase fish production in the African catfish hatchery operations. This study was conducted in August and September 2015 Fish Seed Center (BBI) Bontomanai Gowa in South Sulawesi, The experimental design used was completely randomized design (CRD) with 4 treatments and 3 replications ie Treatment A (1.000 ppm), treatment B (2,000 ppm), treatment C (3,000 ppm), and without giving a solution of PACI - Paci (treatment D). The results showed that soaking in the solution catfish paci paci leaf extract is effective to reduce the infestation Trichodina to 84%, and the best dose in this study with a 24-hour immersion is 3 g / l.dengan this treatment achieved a survival rate higher catfish during immersion, ie 97%.